2020
DOI: 10.1136/jitc-2019-000441
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cell-intrinsic expression of MHC II in lung cancer cell lines is actively restricted by MEK/ERK signaling and epigenetic mechanisms

Abstract: BackgroundProgrammed death 1/programmed death ligand 1 (PD-1/PD-L1) targeted immunotherapy affords clinical benefit in ~20% of unselected patients with lung cancer. The factor(s) that determine whether a tumor responds or fails to respond to immunotherapy remains an active area of investigation. We have previously defined divergent responsiveness of two KRAS-mutant cell lines to PD-1/PD-L1 blockade using an orthotopic, immunocompetent mouse model. Responsiveness to PD-1/PD-L1 checkpoint blockade correlates wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 51 publications
1
27
0
Order By: Relevance
“…Further, CD4+ T cells were activated by CD40-CD40LG and CD28-CD86 interactions in MPR patients. This suggests that although MHC-II expression is usually restricted to APCs, however, MHC-II could also be expressed intrinsically in a subset of cancer cells 83 or induced by IFNγ 29 . Given the low expression of MHC-II in TN patients, it is likely that the expression of MHC-II genes was induced by IFNγ secreted by effector T or NK cells as a result of therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, CD4+ T cells were activated by CD40-CD40LG and CD28-CD86 interactions in MPR patients. This suggests that although MHC-II expression is usually restricted to APCs, however, MHC-II could also be expressed intrinsically in a subset of cancer cells 83 or induced by IFNγ 29 . Given the low expression of MHC-II in TN patients, it is likely that the expression of MHC-II genes was induced by IFNγ secreted by effector T or NK cells as a result of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Given the low expression of MHC-II in TN patients, it is likely that the expression of MHC-II genes was induced by IFNγ secreted by effector T or NK cells as a result of therapy. Recent studies report that inhibition of histone deacetylases (HDAC) and mitogen-activated protein kinase kinase (MEK) enhanced MHC-II expression in NSCLC cell lines 83 . Thus, indicated that promoting antigen presentation via the MHC-II pathway may be a strategy to enhance response to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…It is also notable that responsiveness to PD-1/PD-L1 checkpoint blockage correlates with an interferon gamma-inducible gene signature and major histocompatibility complex class II (MHC II) expression by tumor cells [ 192 ]. Recent data emphasize the active inhibitory role of epigenetic and ERK signaling cascades in restricting cancer cell-intrinsic MHC II expression in NSCLC and suggest their combinatorial inhibition as new responsiveness to checkpoint therapies [ 192 ].…”
Section: New Optimism For Targeting Kras Mutatimentioning
confidence: 99%
“…Because most MSS mCRCs are poorly immunogenic, studies have been performed to overcome this limitation by enhancing immunogenicity using various agents. The mitogen-activated protein kinase pathway is known to modulate the expression of major histocompatibility complex class I molecules, thus regulating antigen presentation during carcinogenesis [ 21 , 76 ]. Mitogen-activated protein/extracellular signal-regulated kinase (MEK) inhibition enhances major histocompatibility complex class I molecule expression and intratumoral T cell infiltration in preclinical CRC models [ 77 , 78 ].…”
Section: Overcoming Resistance To Immunotherapy In Mss/pmmr Mcrc With Novel Combination Strategiesmentioning
confidence: 99%